2016
DOI: 10.5539/elt.v9n6p176
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Lexical Bundles Used by Native and Non-native Scholars

Abstract: In the recent years, globalization prepared a ground for English to be the lingua franca of the academia. Thus, most highly prestigious international journals have defined their medium of publications as English. However, even advanced language learners have difficulties in writing their research articles due to the lack of appropriate lexical knowledge and discourse conventions of academia. Considering the fact that the underuse, overuse and misuse of formulaic sequences or lexical bundles are often character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
19
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 47 publications
12
19
5
Order By: Relevance
“…These results are also similar to those reported by, Hyland (2008a) and Conrad and Biber (2005) for academic writing. But the results in our study are contrary to the finding of Güngör and Uysal (2016) who reported that L1 Turkish writers used more VP-based bundles. These different results might be explained by the use of writing from different L1s, but Chen and Baker (2010) study with L1 Chinese students found that both native and non-native student essays contain many more VP-based bundles than native expert writing does.…”
Section: Structural Characteristicscontrasting
confidence: 99%
See 4 more Smart Citations
“…These results are also similar to those reported by, Hyland (2008a) and Conrad and Biber (2005) for academic writing. But the results in our study are contrary to the finding of Güngör and Uysal (2016) who reported that L1 Turkish writers used more VP-based bundles. These different results might be explained by the use of writing from different L1s, but Chen and Baker (2010) study with L1 Chinese students found that both native and non-native student essays contain many more VP-based bundles than native expert writing does.…”
Section: Structural Characteristicscontrasting
confidence: 99%
“…In spite of the assertion made by Adel and Erman (2012) that L1 writers produce a greater number of and more varied set of lexical bundles, there are a number of studies that have found just the opposite. The results of the present study are in accord with Güngör and Uysal (2016), Pan et al (2016) and Hyland (2008a) on the finding that non-native speakers produced more lexical bundles than native speakers did in academic writing. As Paquot and Granger (2012:139) assert, "[L]earners tend to use more lexical bundles in writing when compared to native speakers ....…”
Section: Types and Tokenssupporting
confidence: 90%
See 3 more Smart Citations